2016
DOI: 10.1007/s11356-016-6054-1
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of antibiotic ciprofloxacin: pathways, influential factors, and bacterial community structure

Abstract: Antibiotic ciprofloxacin is ubiquitous in the environment. However, little is known about ciprofloxacin dissipation by microbial community. The present study investigated the biodegradation potential of ciprofloxacin by mixed culture and the influential factors and depicted the structure of ciprofloxacin-degrading microbial community. Both the original microbiota from drinking water biofilter and the microbiota previously acclimated to high levels of ciprofloxacin could utilize ciprofloxacin as sole carbon and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
65
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(67 citation statements)
references
References 56 publications
2
65
0
Order By: Relevance
“…This increase may indicate an inhibition of the nitrification process. However, during the biodegradation of metformin and ciprofloxacin, several amino groups were generated as by‐products (guanylurea and piperazine rings) that released nitrogen (as ammonia) to wastewater . For this reason, during the degradation of pharmaceuticals there was an increase in the concentration of NH 3 ‐N in the effluent of the aerated biofilter.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This increase may indicate an inhibition of the nitrification process. However, during the biodegradation of metformin and ciprofloxacin, several amino groups were generated as by‐products (guanylurea and piperazine rings) that released nitrogen (as ammonia) to wastewater . For this reason, during the degradation of pharmaceuticals there was an increase in the concentration of NH 3 ‐N in the effluent of the aerated biofilter.…”
Section: Resultsmentioning
confidence: 99%
“…However, during the biodegradation of metformin and ciprofloxacin, several amino groups were generated as by-products (guanylurea and piperazine rings) that released nitrogen (as ammonia) to wastewater. 14,46,52 For this reason, during the degradation of pharmaceuticals there was an increase in the concentration of NH 3 -N in the effluent of the aerated biofilter. A certain amount of this nitrogen is transformed into nitrites, nitrates and nitrogen gas due to biological reactions that occur within the biofilm formed on the F. benjamina wood chips.…”
Section: Effect Of the Removal Of Pharmaceuticals On The Nitrogen Remmentioning
confidence: 99%
“…The degradation pathways of CPX remains a question of debate as it does not get easily degraded except with a particular kind of bacteria (Labrys poetucalensis) (Amorim et al, 2014). Liao et al (2016) suggested that with the increase in temperature, the CPX degradation rapidly increases and the supplement of glucose or nitrogen could improve the degradation rate. However, such scenarios do not sound feasible in the open environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…However, some recent studies have discussed the role of using mixed cultures in degradation (Dorival‐García, Zafra‐Gómez, Navalón, González, & Vílchez, ; Z. Liu, Sun, Pavlostathis, Zhou, & Zhang, ). Certain bacterial groups belonging to the class Proteobacteria have a role in achieving CIP degradation by using it as a carbon and nitrogen source (Liao et al, ). It has also been mentioned that an external source of organic matter holds the potential for better degradation of CIP owing to increased microbial biomass.…”
Section: Introductionmentioning
confidence: 99%